Penggunaan Website Construct Dalam Mengenalkan Dan Cara Membaca Huruf Hijaiyah Di TPA Darul Farhan Palangka Raya - Rendy Adrian; Renaldy Akbar; Hadma Yuliani (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
This article discusses the potential use of websites as a tool for learning Hijaiyah letters, the basis of Arabic writing and the Quran. The purpose of this service is to see explore the role and possibility of utilizing websites in facilitating the learning of Hijaiyah letters. The service was carried out at Darul Farhan TPA using the socialization method and learning approach Using an educative website construct TPA children are introduced to Hijaiyah letters through an educational website that attracts their attention. The use of laptops and smartphones facilitates the identification of Hijaiyah letters, and the “Construct” program is used to measure children's understanding of the letters. The results of the service show that the use of the Construct website in the introduction and learning of Hijaiyah letters at Darul Farhan TPA makes it easy for children to understand Hijaiyah letters.  This learning method also prevents children's boredom by combining learning with games.